Level of Creative Mathematical Thinking among Secondary School Students and its Relationship to Student Achievement - Bahjat Altakhayneh (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
The study aims to investigate the level of mathematical creative thinking among secondary school students and its relationship to their achievement. The study sample consisted of students of the first scientific secondary grade who are registered in the schools of the Capital Governorate, Amman, in Jordan for the academic year 2019/2020. To achieve the objectives of the study, a test of mathematical creative thinking and a test of achievement in mathematics were prepared. The results of the study showed low levels of mathematical creative thinking skills; they were ranked in ascending order as follows: the skill of flexibility (24.38), the skill of originality (24.93), and the skill of fluency (25.13). The average of creative mathematical thinking in general was (74.44). The results of the study do not show a correlation between the variables of mathematical creative thinking and achievement, nor a difference between the average scores of students in mathematical creative thinking due to gender and school type. In light of the results, the researcher recommends the necessity to prepare programs to develop creative thinking in mathematics..